Optimasi biaya distribusi talenan menggunakan algoritma heuristik penghematan Clark dan Wright (studi kasus di PT Titan) - Lutpi Abdul Latip (Perspectives in Mathematics and Applications, 2025)
One of the main challenges in PT Titan’s distribution process is the inaccurate determination of vehicle routes and improper selection of vehicle types and capacities, which leads to inefficient distribution costs. Although PT Titan already has a distribution route, the author proposed a more cost-effective alternative using the Clark and Wright Saving Heuristic, which efficiently solves vehicle routing problems by allowing a single vehicle to serve multiple agents in a single trip. The research aimed to identify the current distribution routes for cutting board products, apply the algorithm to improve them, and determine the most optimal routes after optimization. Graphs were used to visualize the revised distribution plan. The results showed two significant optimizations in mileage and cost. For the L300 and Ankle Box vehicles, mileage was reduced by 9 km, and distribution costs were reduced by 2.8% (Rp 250,000 per trip). Meanwhile, the Double ankle and L300 vehicles achieved a mileage reduction of 55.13%, corresponding to 1,386 km. They cost savings of 28.1% or Rp2.500,000 The final optimized routes consist of Route 1 (Depot–Klaten–Boyolali–Depot) and Route 2 (Depot–Bogor–Tangerang–Depot) using Doubel ankle vehicle, and Route 3 (Depot–Kuningan–Cikijing–Depot) using an L300 vehicle, resulting in a more efficient and cost-effective distribution system for PT Titan.